Arbitrium Humanum: Liberum vel Liberandum? An Historical-Theological Study of John Calvin's Doctrine of the Will - Van, Vliet P. Jason (My University, 2005)
John Calvin, the sixteenth-century reformer, taught that the fall into sin left the human will bound in a miserable slavery to depravity, unless it is liberated by Jesus Christ. Recently, Dewey J. Hoitenga Jr. has argued that Calvin retains so little of the will as it was created that he cannot adequately account for humanity's moral responsibility. However, a careful examination of Calvin's writings reveals that this reformer develops an understanding of the human will which is more nuanced than Hoitenga would lead one to believe. Like his mentor, Augustine, Calvin distinguishes between a will that is free from external coercion and a will that is equally free to choose either good or evil. In his debate with the Roman Catholic theologian, Albert Pighius, Calvin upholds the former while rejecting the latter. Furthermore, in this same debate, Geneva's reformer voices his agreement with the libertqs in externis - the liberty of the will in earthly matters - as it is expressed, for instance, in the Augsburg Confession Calvin also ardently avoids the kind of deterministic fatalism which some radical reformers, particularly the Libertines, adopted. At the same time, none of these distinctions and qualifications detract him from his fundamental conviction that the fallen human will, of itself, cannot even begin to take the first steps towards salvation. Redemption is not a co-operative venture between the will of God and the will of human beings. Rather, it includes a sovereign work of God's grace upon the human will. Hoitenga's critique raises important questions; however, it fails to pay sufficient attention to the historical and polemical context in which Calvin develops his doctrine of the will. when that context is investigated, it becomes clear that Calvin teaches the depravity, not the destruction, of the human will. A depraved will cannot save itself, but it remains morally responsible for the actions it initiates.